(untitled) (BIRDEM Medical Journal, 2025)
Liver abscess due to perforation of the gastrointestinal tract by a foreign body is a rare and possibly fatal event. Diagnosing this pathology is complicated by the lack of specific symptoms and ignorance of ingestion by the patient and low clinical suspicion of this condition. The authors report a case of 35-year-old woman who was admitted with abdominal pain and fever. Further investigation revealed hepatic abscess, without resolution despite antibiotic therapy, secondary to fish bone ingestion with consequent piercing of the lesser gastric curvature which was diagnosed by surgery. The literature concerning foreign body-induced perforation of the gastrointestinal tract complicated by liver abscess is reviewed. BIRDEM Med J 2025; 15(1): 51-54